Acute Effects of White Button and Shiitake Mushroom Powder Supplementation on Postprandial Lipemia and Glycemia Following a High-Fat Meal. (14th June 2022) - Talal, Lillian; Horvath, Peter; Wang, Huipei
Abstract: Objectives: To determine the acute effects on postprandial lipemia (PPL) and glycemia (PPG) by supplementing a high-fat meal with either White Button (WB) or Shiitake (SH) mushroom powder. Methods: Nine healthy participants (5 female and 4 male, 23.3 ± 1.3 yr,  17.8 ± 6% body fat,  56.2 ± 11.4 kg fat free mass) were randomized to receive three different meals in a double-blind fashion. Each meal consisted of an 8 oz. cooked beef patty and a bun (883 kcal, 47 g fat, 37.5 g carbohydrate, 73.2 g protein). The control meal was not supplemented with any mushroom powder. The other two meals had 14 g of either WB or SH dried mushroom powder incorporated into the beef patty prior to cooking. Participants fasted for 12 hours and avoided vigorous exercise the day prior to eating a treatment or control meal. Blood was drawn before meal consumption (Time = 0 hours) and every two hours after consumption for a total of six hours (Time = 2, 4, 6 hours). Lipid and glucose panels were performed following meal consumption. Data were analyzed using linear mixed effects models on the outcomes triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and glucose. Fixed effects were gender, meal type, time, and meal type by time interaction, while a random intercept accounted for the variability in the outcomes among the participants. Results: LDL levels were significantly lower for both SH and WB meals compared to the control meal (p = 0.0007) over the course of six hours. Meal type did not affect triglyceride, HDL, and glucose levels. Gender affected triglyceride and HDL levels over the treatment course. Triglyceride levels were significantly higher in males (p = 0.0084) and HDL levels were significantly lower in females (p = 0.0005). Triglyceride and glucose levels were significantly higher, (p < 0.001 and p < 0.0001 respectively), during the postprandial time course (Time = 0, 2, 4, 6 hours). Conclusions: Both SH and WB mushrooms may be important to supplement in the diet to lower serum LDL levels. Future studies are needed to evaluate which of the two treatments is the more potent. Funding Sources: Dedicated to Matthew J Morris, deceased, whose contributions were crucial to this work.